Aspiring Indonesia—Expanding the Middle Class - World Bank (World Bank, Washington, DC, 2020)
Indonesia has seen tremendous progress in poverty reduction over the past couple of decades and, as a result, has made a successful transition from low-income to middle-income country status. As millions have moved out of poverty and extreme poverty, we have also witnessed the rise of Indonesia’s middle class, which now accounts for 20 percent of the total population, or 52 million Indonesians. This group important for Indonesia’s upward trajectory, but it still too small for the ambitions of Indonesia. Expanding the middle class will boost economic growth, strengthen an influential constituency for better governance, and widen and deepen the tax base. An expansion of the middle class, if accompanied by continued growth in the incomes of the poor and vulnerable, will also help to decrease inequality and prevent polarization of the country. One of the key development questions that Indonesia faces is how to expand the middle class. What will be required to bring the 115 million people who are no longer in poverty and vulnerability into the middle class? The future of Indonesia lies partly in the fate of this aspiring middle class, 45 percent of the population, so that they can both share in and help to drive the country’s growing prosperity. Government policy can play an instrumental role in expanding the middle class. This can be done by increasing the level and quality of education, and the skills of the population, and making sure there are well-paid jobs waiting for those in the aspiring middle class. It also means ensuring access to social protection to help lift these aspirers into the middle class and keep them there once they arrive, as well as improving the quality of the public services upon which they currently depend. Resolve to expand the middle class will place greater stress on government budgets. The government will need increasingly rely on the middle class, whose income taxes will finance much of the investment that a growing Indonesia will need. This will require a new social contract with the current – and future – middle class so that they will embrace the policies that both benefit themselves while also helping to expand their ranks, rather than closing off opportunities for others, and creating political polarization—as has occurred in some countries in the region in recent years.